The science of adapted throws: a systematic search and narrative evidence synthesis - Garcia-Carrillo, Exal; Lasso-Quilindo, Cristian Alexis; Chalapud-Narváez, Luz Marina; Castillo-Paredes, Antonio; Farías-Valenzuela, Claudio; Alarcón-Rivera, Miguel; Yáñez-Sepúlveda, Rodrigo; Judge, Lawrence W. (Frontiers in Sports and Active Living, 2025)
IntroductionParalympic throwing events have grown rapidly, yet the scientific evidence guiding technique, training and classification remains fragmented across biomechanics, physiology and psychosocial domains.ObjectiveTo provide an evidence-based overview of adapted throws by comprehensively examining the peer-reviewed literature.MethodsA systematic search of PubMed, Scopus, and Web of Science (inception—Feb 2025) using the terms Paralympic OR adapted OR disability AND throw AND (shot OR discus OR javelin OR club). Inclusion criteria comprised: (i) Athletes with physical impairments who participate in Para Athletics throwing events, (ii) Non-disabled individuals studied in research explicitly designed to inform or understand Para Athletics throwing techniques. Data were synthesized narratively and clustered by study theme.ResultsNineteen studies (n = 345 para athletes; 14 sport classes) met the criteria. Biomechanical analyses identified release velocity (8.3–10.0 m·s−1 in F52–F55 shot put) and optimal angles (27.5°–37°) as key performance determinants. Assistive devices improved results by 8% in F32 athletes. Significant research gaps exist for visual impairment (F11–F13), intellectual impairment (F20), and prosthesis-user classes (F61–F64).ConclusionWhile class-specific technical models are emerging, particularly for seated throwers, 38% of throwing classifications lack published research. Future studies should prioritize underrepresented classes and develop standardized assessment protocols.